On the Development of Cartography of the Uzbekistan SSR in 1920-1950 (Eurasian Scientific Herald, 2022)
The article is devoted to the study of the work done in Uzbekistan in the field of cartography in the 20-50s of the XX century, the creation of educational maps and network atlases. To know and study one's homeland and its territories, one must first have a cartographic image of it. For this reason, the focus on geographic maps is increasing today. The article describes the emergence of scientific societies and institutions engaged in cartography, the problems in their activities, the data on the shortcomings